A Financial Management Model for Sme Owners to Ensure Business Sustainability: The Role of Financial Literacy - Christian Daniel Manu; Jems Arison Zacharias; Ellon Belwan Cornelius Mau; Angela Merici Minggu (Journal of Economic Education and Entrepreneurship Studies, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting economic growth and sustainable development, particularly in developing countries such as Indonesia. Despite their substantial contribution to employment and national income, many MSMEs continue to experience difficulties in maintaining business sustainability due to weak financial management practices and limited financial competence. This study aims to examine the influence of financial literacy and financial capability on MSME business sustainability through the mediating role of financial management. A quantitative approach was employed using a survey method involving 98 MSME owners located in Kupang, Kupang Regency, and South Central Timor Regency. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that financial literacy and financial capability positively and significantly affect financial management practices among MSMEs. Financial management also has a significant positive effect on business sustainability. Furthermore, financial management fully mediates the relationship between financial literacy and business sustainability, while financial capability directly influences sustainability without mediation. These findings emphasize that MSME sustainability depends not only on financial knowledge but also on the practical capability to implement effective financial management strategies. The study highlights the importance of implementation-oriented financial empowerment programs to strengthen MSME resilience and long-term business sustainability.